Prevalence of post-ureterorenoscopy fever in catheterized versus non-catheterized patients - Sarwar, Nubair; Haroon Sabir Khan; Naveed Sarwar; Syed Yazdan Haider; Hassaan Sajid; Rafat Rasheed (International Journal of Pathology, 2026)
Background: Ureterorenoscopy (URS) is commonly performed for ureteric stones, and Foley catheterization is often used postoperatively. However, catheterization may increase the risk of catheter-associated infections and postoperative fever. This study aimed to compare the prevalence of post-URS fever within 24 hours between patients who underwent postoperative Foley catheterization and those who did not undergo Foley catheterization following ureterorenoscopy. Methods: This comparative observational study was conducted at the Armed Forces Institute of Urology, Rawalpindi, including 60 patients undergoing URS for single ureteral stones <15 mm. Patients were allocated into catheterized (n=30) and non-catheterized (n=30) groups. Post-URS fever was defined as oral temperature >100°F within 24 hours. Data were analyzed using SPSS v25. Chi-square tests were used to compare fever prevalence between groups (p<0.05 significant). Results: The mean age was 48.8±10.3 years; 63.3% were male. Groups were comparable in age, gender, stone size, location, and URS duration (p>0.05). Overall, 8 patients (13.3%) developed post-URS fever. Fever prevalence was significantly higher in the catheterized group compared to the non-catheterized group (20.0% vs 6.7%, p=0.028). Stratification showed trends toward higher fever in females, stones ≥10 mm, and longer operative duration (>35 min), though not statistically significant (p>0.05). Conclusion: Foley catheterization after URS is associated with a prevalence of postoperative fever. Selective, patient-specific catheter use is recommended to minimize morbidity.